Analysis of platelet and monocyte-to-lymphocyte ratio and diabetes mellitus with benign prostatic enlargement - Chen, Guanheng; Feng, Leiguang (Frontiers in Immunology, 2023)
Background: The etiology of benign prostatic hyperplasia (BPH) is still elusive. The aim of this study was to provide preventive and prognostic parameters associated with diabetes mellitus with benign prostatic enlargement (BPE).Methods: Diabetic patients were collected retrospectively from February 2021 to December 2022, including monocyte-to-lymphocyte ratio (MLR). Diabetic patients were divided into two groups by whether the prostate volume was greater than or equal to 30 ml, which were diabetes mellitus without BPE (DM) and diabetes mellitus with BPE (DM+BPE). The baseline characteristics were compared, the risk and protective factors associated with DM+BPE were determined using univariate and multivariate logistic regression, and the parameters associated with prostate volume were determined using correlation analysis.Results: Of the 671 patients collected, age and prostate volume were significantly higher in the DM+BPE than in the DM; MLR was higher in the DM+BPE than in the DM; and platelet was significantly lower in the DM+BPE than in the DM. Univariate logistic regression showed that age was a risk factor, while protective factors for DM+BPE were lymphocytes and platelet. Multifactorial logistic regression showed that age was a risk factor, while platelet was the protective factor for DM+BPE. In the total overall (n=671), prostate volume was positively correlated with age. Prostate volume was negatively correlated with lymphocytes and platelet. In DM+BPE (n=142), prostate volume was positively correlated with age and MLR.Conclusion: Platelet was a protective factor for DM+BPE and was negatively correlated with prostate volume, whereas MLR was positively correlated with prostate volume in DM+BPE.